2022
DOI: 10.1186/s42358-022-00267-y
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for evaluation and diagnosis of extra-glandular manifestations of primary Sjögren syndrome: results of an epidemiologic systematic review/meta-analysis and a consensus guideline from the Brazilian society of rheumatology (hepatic, gastrointestinal and pancreatic)

Abstract: Sjogren's syndrome (SS) is an autoimmune disease characterized by lymphocytic infiltration of the exocrine glands and other organs, associated with sicca syndrome but also with systemic involvement with varying degrees of severity. Despite their importance, some systemic manifestations, mainly liver, gastrointestinal, and pancreatic are not routinely evaluated. To address these manifestations, the Sjögren's Syndrome Committee of the Brazilian Society of Rheumatology conducted a broad systematic review of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…In order to evaluate the efficacy more comprehensively, we chose both ESSDAI and ESSDAI as the index of subjective symptoms and systemic characteristics that showing to be valid and sensitive measures 37 . Furthermore, it is interesting to underline that, in the present study, the variety immunological indexes were accordant with subjective indexes 38 . The association between them could be explained inflammatory reaction play a leading role in disease mechanism.…”
Section: Discussionsupporting
confidence: 61%
“…In order to evaluate the efficacy more comprehensively, we chose both ESSDAI and ESSDAI as the index of subjective symptoms and systemic characteristics that showing to be valid and sensitive measures 37 . Furthermore, it is interesting to underline that, in the present study, the variety immunological indexes were accordant with subjective indexes 38 . The association between them could be explained inflammatory reaction play a leading role in disease mechanism.…”
Section: Discussionsupporting
confidence: 61%
“…Patients diagnosed with PBC exhibit a prevalence of pSS of approximately 38%. However, clinical evidence of PBC is observed in fewer than 2% of patients with SS, according to large cohort studies (Trevisani et al, 2022). In instances where SS is accompanied by liver dysfunction, treatment usually involves the isolated use of hepatoprotective drugs such as ursodeoxycholic acid, aimed at symptomatically improving liver function.…”
Section: Liver Involvementmentioning
confidence: 99%
“…Initially, abatacept was found to lessen inflammation and enhance saliva production in SS (Meiners et al, 2014), with subsequent ROSE and ROSE II trials confirming improvements in various outcomes, including glandular, extraglandular, and systemic manifestations (Tsuboi et al, 2023). However, despite these biological effects on biomarkers and immune cells, a phase III trial in active primary SS indicated that abatacept did not achieve significant clinical efficacy compared to placebo (Baer et al, 2021;van N et al, 2020).…”
Section: Application Of Abatacept In Ssmentioning
confidence: 99%
“…Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disease that affects the exocrine glands, such as the lacrimal and the salivary glands ( 1 3 ). In addition, various extraglandular lesions may occur in the lung, the kidney, the joints, or the lymph nodes in many patients with this syndrome ( 4 , 5 ). Systemic symptoms in pSS patients are well known and include arthralgia, fatigue, general discomfort, and cardiovascular events ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%